2018
DOI: 10.1111/brv.12399
|View full text |Cite
|
Sign up to set email alerts
|

Amyloids of multiple species: are they helpful in survival?

Abstract: Amyloids are primarily known for their roles in neurodegenerative disorders, as well as in systemic diseases like diabetes. Evolutionary forces tend to maintain a healthy set of heritable characteristics, while eliminating toxic or unfavourable elements; but amyloids seem to represent an exception to this fundamental concept. In addition to their presence in mammals, amyloids also persist in the proteome of many lower organisms that may be linked with possible roles in survival, which are still unexplored. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 391 publications
(435 reference statements)
0
8
0
Order By: Relevance
“…Currently, researchers are mainly focused on drugs that can minimize the synthesis and aggregation of Aβ and/or decrease tau phosphorylation. Molecules targeting cholinesterase and preventing the formation of amyloidic aggregates in the brain tissues could be the other set of possible drug candidates. , Furthermore, statins, cholesterol-lowering drugs, anti-inflammatory substances, antioxidants molecules, and antibody-based treatment plans have also been investigated thoroughly in the past few decades to lower the symptoms and improve the quality of life of the patients. Further elucidation of AD etiology to discover novel therapeutic molecules capable of blocking AD progression efficiently and developing strategies to deliver to the regions against BBB may be helpful. Numerous clinical data suggested that impairment of cholinergic–neurotransmitter systems, possibly due to the suppression of acetylcholine (crucial for neural synapse) by acetylcholinesterase (AChE) activity and activation of the glutamatergic system, also plays a very aggressive role in AD pathology. , In recent years, acetylcholinesterase inhibitors (AChEI) and N -methyl- d -aspartate (NMDA) receptor antagonists are recognized as a potential therapeutic intervention to counter the disease-linked perturbances …”
Section: Essentials Of Alzheimer’s Disease: Genetics Etiology Pathway...mentioning
confidence: 99%
“…Currently, researchers are mainly focused on drugs that can minimize the synthesis and aggregation of Aβ and/or decrease tau phosphorylation. Molecules targeting cholinesterase and preventing the formation of amyloidic aggregates in the brain tissues could be the other set of possible drug candidates. , Furthermore, statins, cholesterol-lowering drugs, anti-inflammatory substances, antioxidants molecules, and antibody-based treatment plans have also been investigated thoroughly in the past few decades to lower the symptoms and improve the quality of life of the patients. Further elucidation of AD etiology to discover novel therapeutic molecules capable of blocking AD progression efficiently and developing strategies to deliver to the regions against BBB may be helpful. Numerous clinical data suggested that impairment of cholinergic–neurotransmitter systems, possibly due to the suppression of acetylcholine (crucial for neural synapse) by acetylcholinesterase (AChE) activity and activation of the glutamatergic system, also plays a very aggressive role in AD pathology. , In recent years, acetylcholinesterase inhibitors (AChEI) and N -methyl- d -aspartate (NMDA) receptor antagonists are recognized as a potential therapeutic intervention to counter the disease-linked perturbances …”
Section: Essentials Of Alzheimer’s Disease: Genetics Etiology Pathway...mentioning
confidence: 99%
“…However, some lines of studies suggest that the unwanted accumulation of the different proteins into inclusion bodies is nothing more than an event of an age-bound decline in the activity and efficiency of cellular PQC systems, causing a plethora of systemic and nonsystemic pathologies, among which neurodegenerative diseases (NDDs) are the most common (Knowles and others 2014). Nevertheless, the occurrence of similar proteinaceous structures in prokaryotes, lower organisms, and different classes of higher animals further substantiates the notion that the formation of IBs is an evolutionarily conserved mechanism that may have meaningful structural and functional roles in the survival of organisms (Shively and others 2001; Upadhyay and Mishra 2018).…”
Section: Introductionmentioning
confidence: 57%
“…However, protein aggregation is not always pathological. Many organisms, including bacteria, invertebrates, and mammals, have proteins that can only perform their functions after polymerizing or forming amyloid aggregates (reviewed by Fowler and others 2007; Upadhyay and Mishra 2018).…”
Section: The Aggregation Landscape: Why Do Neurons Die First?mentioning
confidence: 99%
“…Amyloids are highly stable non-covalent protein aggregates that possess a set of specific structural features [for reviews see Baxa, 2008 andUpadhyay &Mishra, 2018]. Such aggregates are produced from abnormally folded protein molecules, and are able to self-perpetuate by the following mechanism (Prusiner, 1998;Wickner et al, 2000;Liebman & Chernoff, 2012).…”
Section: (8) Switch Of Protein Conformation From Native To Amyloidmentioning
confidence: 99%